Lumine [Vol. 1] - Krogell, Emma (WEBTOON Unscrolled, a division of Wattpad WEBTOON Studios, Inc., 2023)
"In a world where weredogs, witches, and humans live side by side, Lumine is a down-on-his-luck weredog with nowhere to turn--until he meets antisocial witch boy Kody. Lumine also has a big, fluffy, secret--he is actually a werewolf, a rare and more powerful type of magical being thought to be extinct. Except...he can't transform properly. When robbers attach the two boys, Lumine shifts into his other form: a tiny, fierce, and ridiculously cute puppy dog. Impressed with the small-but-mighty pup, Kody's dad hires Lumine to be his son's bodyguard. Lumine is determined to both protect Kody and become his friend, but the mysterious witch does everything in his power to keep Lumine at arm's length. Without realizing, Lumine has stumbled paws first into a family of dangerous secrets."--from back cover.